Working capital and performance: Europe’s challenge to crises - Zanolla, Ercilio; Pimentel, Pedro; Couto, Gualter (Journal of Business Economics and Management, 2024)
This paper explores the relationship between working capital management (WCM) strategies and business performance during the COVID-19 crisis. Data from 1,067 non-financial European firms from 33 countries distributed across 6 economic sectors in the period from 2015 to 2021, feed Ordinary Least Squares model (OLS), robust and quantile pooled regression. COVID-19 crisis seems to have negatively influenced only median-low-range performance firms in Europe, showing that crisis coming from productive capacity hibernation do not impact nor impose tough slow recovery, transversal to all firms, as occurred on other financial crises. As for WCM, only median-top-range performance firms had significant statistical evidence for negative impact, that become positive for median-range performance firms during COVID-19. For Eurozone firms, there was an additional positive influence of the WCM on performance during COVID-19. Median-range performance firms seems to benefit from conservative WCM strategies mitigating firms’ performance negative effect raised by COVID-19 crisis. Relation between COVID-19 and WCM seems to be sensitive to different levels of firms’ performance and to different business’ economic sector. Contrary to knowledge on WCM, performance and financial crises in Europe, for COVID-19 alike crises, performance benefits from higher cash conversion cycles and thus encourage conservative WCM strategies. Liquidity should not be pushed by adopting aggressive WCM strategies.